Breast reconstruction after mastectomy among Department of Defense beneficiaries by race. Issue 19 (25th June 2014) - Enewold, Lindsey R.; McGlynn, Katherine A.; Zahm, Shelia H.; Poudrier, Jill; Anderson, William F.; Shriver, Craig D.; Zhu, Kangmin
Abstract : BACKGROUND: Postmastectomy breast reconstruction increased approximately 20% between 1998 and 2008 in the United States and has been found to improve body image, self‐esteem, and quality of life. These procedures, however, tend to be less common among minority women, which may be due to variations in health care access. The Department of Defense provides equal health care access, thereby affording an exceptional environment in which to assess whether racial variations persist when access to care is equal. METHODS: Linked Department of Defense cancer registry and medical claims data were used. The receipt of reconstruction was compared between white women (n = 2974) and black women (n = 708) who underwent mastectomies to treat incident histologically confirmed breast cancer diagnosed from 1998 through 2007. RESULTS: During the study period, postmastectomy reconstruction increased among both black (27.3% to 40.0%) and white (21.8% to 40.6%) female patients with breast cancer. Receipt of reconstruction did not vary significantly by race (odds ratio, 0.93; 95% confidence interval, 0.76‐1.15). Reconstruction decreased significantly with increasing age, tumor stage, and receipt of radiotherapy and was significantly more common in more recent years and among active servicewomen, TRICARE Prime (health maintenance organization) beneficiaries, and women whose sponsor was an officer. CONCLUSIONS: The receipt of breast reconstruction did not vary by race within this equal‐access health system, indicating that the racial disparities reported in previous studies may have been due in part to variations in access to health care. Additional research to determine why a large percentage of patients with breast cancer do not undergo reconstruction might be beneficial, particularly because these procedures have been associated with noncosmetic benefits. Cancer 2014;120:3033–3039. Published 2014. This article is a U.S. Government work and is in the public domain in the USA. Abstract : The receipt of reconstruction did not vary by race within this equal‐access health system, indicating that the racial disparities reported in previous studies may have been due in part to variations in health care access.